Residuos, degradación y comportamiento de la ametrina en un vertisol de Guanacaste. Costa Rica - León Dobles, Lorena (1978)
Residues of the herbicide Ametrine (2-ethylamine-4-isopropylamine-6-methylthio-s-atrazine) were determined by UV-spectrometrical analysis in a soil (vertisol) of Guanacaste, Costa Rica, which has been treated with this herbicide for the past six years. Sugar cane was the only crop cultivated. 3 Kg/ha of 80 percent Ametrine was the last application, 240 days before sampling. Ametrine residues up to 1.10 ppm were found. The higher values generally correspond to higher contents of montmorillonite clay. The adsorption of the herbicide by the soil is high, 50-78 percent, and was characterized by a Freundlich-type isothermal equation. The degradation of Ametrine in this soil shows a rate of approximately 0.1 ppm every 20 days. This decomposition is considered slow compared with similar studies in other soil types.